2014
DOI: 10.1016/j.otsr.2013.12.017
|View full text |Cite
|
Sign up to set email alerts
|

John Thomas sign – a memorable but misleading sign in hip fractures

Abstract: Level III Case control study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…They retrospectively reviewed AP pelvis radiographs of 200 males, of which 100 had a hip fracture and 100 were controls. Their results showed only an accuracy of 46%, and their conclusions determined that this sign is no better than the toss of a coin in relation to hip fractures [11]. These findings are similar to a study conducted by Ya'ish and Baloch who retrospectively reviewed pelvic radiographs of 100 males with hip fractures and compared them with 100 males without hip fractures, and noted the direction of penile shadowing with a sensitivity of only 30% [13].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…They retrospectively reviewed AP pelvis radiographs of 200 males, of which 100 had a hip fracture and 100 were controls. Their results showed only an accuracy of 46%, and their conclusions determined that this sign is no better than the toss of a coin in relation to hip fractures [11]. These findings are similar to a study conducted by Ya'ish and Baloch who retrospectively reviewed pelvic radiographs of 100 males with hip fractures and compared them with 100 males without hip fractures, and noted the direction of penile shadowing with a sensitivity of only 30% [13].…”
Section: Discussionsupporting
confidence: 64%
“…Unfortunately, there is little substantial evidence within the literature regarding the use of pelvic shadowing as a reliable soft tissue change to predict laterality of hip pathology or injury. Several studies have failed to demonstrate a correlation between pelvic shadowing and hip fracture laterality, with one study describing this sign as "less accurate than the toss of a coin" [11][12][13][14][15]. Murphy et al attempted to find a relationship between pelvic shadowing and not only with hip fracture side but also penile size and angulation.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that a penile shadow would point to the side of fracture in a pelvis, and this is considered a positive John Thomas Sign (Murphy, Murphy, & Heffernan, 2014;Thomas, Lyons, & Walker, 1998). However, it is inconclusive in this case report because there are bilateral fractures in the pelvis, and the penis pointed to the left side.…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivities and specificities were extracted from the relevant studies, 4 ,5,8-14 where available. These values were used to calculate the Log Odds Ratio and associated 95% confidence model for each study.…”
Section: Data Synthesis and Statistical Analysismentioning
confidence: 99%
“…This sign is defined as positive, when the penile shadow points towards the side of a hip or pelvic fracture in male patients. 4 Few studies have objectively described the diagnostic value of the JTS. There is, however, a need to explore the literature regarding this sign as some studies have suggested a 'higher than chance' correlation between the JTS and a unilateral hip fracture.…”
Section: Introductionmentioning
confidence: 99%